Biometric and Ligaments Analysis of the Scaphotrapeziotrapezoid Joint: Implications for Arthroplasty - Albert, Thomas; Bellemère, Philippe; Atzei, Andrea; Ardouin, Ludovic (Journal of Wrist Surgery, 2025)
The periarticular ligament anatomy of the scaphotrapeziotrapezoid (STT) joint varies in the literature, complicating standardization. Preservation of this ligamentous array is critical in preventing intracarpal malalignment.This study aims to map ligament insertion sites on the bony components of the STT joint and define resection margins for the scaphoid, trapezium, and trapezoid during arthroplasty.We examined 26 cadaveric wrists. Needles marked the STT joint before arthrotomy, allowing precise observation of ligament positioning intact. Ligament insertion sites on the scaphoid, trapezium, and trapezoid were measured with micrometric calipers. We recorded STT arthritis presence and distribution on the scaphoid, trapezium, and trapezoid articular surfaces. Each surface was divided into four quadrants voloulnar (VU), voloradial (VR), dorsoulnar (DU), and dorsoradial (DR).The dorsal intercarpal ligament (DIC) was the only extrinsic dorsal ligament of the STT joint. The average insertion distance from the articular surface was 3.033 mm (standard deviation [SD] = 0.693) on the trapezium and trapezoid, compared to 1.918 mm (SD = 0.329) on the scaphoid. This difference was statistically significant (p < 0.001). The palmar ligament organization resembled a rigid tripod anchored by the RS (radioscaphoid), ST (scaphotrapezial), and SC (scaphacapitate) ligaments around the scaphoid tubercle. Palmar ligament insertion points averaged 0.58 mm (SD = 0.32) from the articular surface, with no significant difference between the scaphoid and the trapezoid–trapezium complex (p = 0.558). STT arthritis was present in 80.8% of wrists. The VU sides of the STT were most affected, particularly the volar side of the trapezoid.The DIC ligament and palmar ligamentous tripod, formed by the RS, SC, and ST ligaments, could acts as a mechanical lock preventing dorsal scaphoid translation. While distal scaphoid pole resection is standard, our findings suggest prioritizing proximal trapezium and trapezoid resections in arthroplasty to avoid instability.
Keywords: STT joint; wrist ligaments; arthroplasty; anatomy; arthritis